3D cutting force analysis in worn-tool finish hard turning. (27th October 2008) - Hu, Jianwen; Song, Hui; Chou, Y. Kevin
This study develops an analytical model for cutting force simulations in finish hard turning by a worn tool, which includes both chip formation and flank wear-land contact forces. Due to the 3D nature of the cutting zone, both the uncut chip area and wear-land contact are considered as numerous thin slices and individually analysed for cutting forces modelling. Using coordinate transformations, cutting forces due to individual slices can be projected and further integrated from the lead to tail cutting edge to calculate three components of cutting forces. The methodology was applied to simulate process parameter effects on cutting forces. The radial component is the most sensitive force to the change of process parameters, especially, flank wear-land and tool nose radius. Among all parameters tested, flank wear-land shows the most dominant effects on cutting forces and its existence will also augment the effects of other parameters, for example, the tool nose radius.